2011
DOI: 10.3171/2010.8.jns10298
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural hematoma in the elderly: not a benign disease

Abstract: Object Chronic subdural hematoma (CSDH) is perceived to be a “benign,” easily treated condition in the elderly, but reported follow-up periods are brief, usually limited to acute hospitalization. Methods The authors conducted a retrospective review of data obtained in a prospectively identified consecutive series of adult patients admitted to their institution between September 2000 and February 2008 and in whom there was a CT diagnosis of CSDH. Survival data were compared to life-table data. Results Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
183
5
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(225 citation statements)
references
References 20 publications
13
183
5
9
Order By: Relevance
“…The overall survival of patients in the surgical group was higher than that of patients in the conservative group. Although several studies have shown an increase in mortality rates associated with drainage of chronic SDHs in elderly patients, 9,14,18 the results of our study have shown that surgical drainage is associated with a long-term overall survival benefit even in patients aged over 90 years old.…”
Section: Survival Outcomesmentioning
confidence: 49%
“…The overall survival of patients in the surgical group was higher than that of patients in the conservative group. Although several studies have shown an increase in mortality rates associated with drainage of chronic SDHs in elderly patients, 9,14,18 the results of our study have shown that surgical drainage is associated with a long-term overall survival benefit even in patients aged over 90 years old.…”
Section: Survival Outcomesmentioning
confidence: 49%
“…6 One large scale study revealed its mean age of occurrence as 80.6 years. 7 However in our case the patient was relatively young. It usually occurs after a trivial injury though a history of direct trauma to the head is absent in up to half the cases.…”
Section: S128mentioning
confidence: 53%
“…It usually occurs after a trivial injury though a history of direct trauma to the head is absent in up to half the cases. 7 There is no damage to the underlying brain and usually there is a period of weeks to months before it becomes clinically evident and then these patients of CSDH usually present with various neurological signs and symptoms However, uniquely, in our patient, the only presenting sign was just an isolated oculomotor nerve palsy. Isolated oculomotor nerve palsy occurring in association with subdural haematoma is in itself, a rare finding.…”
Section: S128mentioning
confidence: 57%
“…The Chronic SDH is benign condition with mortality is less than 2% while the leptomeningeal disease is associated with almost 100% mortality (6,7,8).…”
Section: Discussionmentioning
confidence: 99%